2001
DOI: 10.1001/archneur.58.11.1891
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Studies in a Family With Probable X-linked Dominant Charcot-Marie-Tooth Disease Involving the Central Nervous System

Abstract: This family differs from others with hereditary motor and sensory neuropathic diseases by the presence of upper motor neuron signs and additional features. The clinical features and inheritance pattern are consistent with X-linked dominant inheritance or autosomal dominant inheritance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Previously, CMTX patients were reported with white matter lesions in the periventricular area, the parietal white matter, and in the splenium of corpus callosum (6)(7)(8). Among them, only one male case showed scattered white matter lesions that were similar to those in our case (6) (12). Although sequence variants in the GJB1 promoter region were detected in this case, direct DNA sequencing of the GJB1 coding region was normal (12).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Previously, CMTX patients were reported with white matter lesions in the periventricular area, the parietal white matter, and in the splenium of corpus callosum (6)(7)(8). Among them, only one male case showed scattered white matter lesions that were similar to those in our case (6) (12). Although sequence variants in the GJB1 promoter region were detected in this case, direct DNA sequencing of the GJB1 coding region was normal (12).…”
Section: Discussionsupporting
confidence: 65%
“…Among them, only one male case showed scattered white matter lesions that were similar to those in our case (6) (12). Although sequence variants in the GJB1 promoter region were detected in this case, direct DNA sequencing of the GJB1 coding region was normal (12).…”
Section: Discussionsupporting
confidence: 60%
“…Brain MRI was available on BAB8201 in which diffuse hyper‐intensity in the white matter on T2‐weighted images suggestive of hypomyelination, thin corpus callosum and reduced brain volume were detected. Clinical information from the family of BAB8201 with positive family history was published separately (Hisama et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, fixed spasticity, hyperreflexia, dysarthria and ataxia have also been reported. [102, 107, 109, 110] A number of studies have reported MRI imaging abnormalities in CMT1X patients. In most cases, these imaging abnormalities are accompanied by clinical findings, [91, 102, 108, 109] while in at least two case no mention is made of accompanying clinical signs or symptoms [111, 112] Interestingly, two reports [102, 109] describe diffuse involvement of the corticospinal/corticobulbar tracts, suggesting that this tract may represent a selectively vulnerable region; the predominance of findings indicative of corticospinal dysfunction in patients with fixed abnormalities, and the predominance of corticospinal findings in patients with florid acute syndromes (see below) also suggest this possibility.…”
Section: Disease Manifestations Of Gjb1 Mutationsmentioning
confidence: 99%